Uji Aktivitas Antibakteri Ekstrak Etanol Lidah Buaya (Aloe vera (L.) Burm. f.) terhadap Propionibacterium acnes dan Pseudomonas aeruginosa - Iwasil, Prishcilia; Mambo, Christi D.; Posangi, jimmy; Homenta, Heriyannis; Nangoy, Edward; Masengi, Angelina S. R. (e-CliniC, 2025)
Abstract: Aloe vera (Aloe vera (L.) Burm. f.) is recognized for its antibacterial potential, particularly against skin infection-causing bacteria such as Propionibacterium acnes and Pseudomonas aeruginosa. Skin infections pose a significant health issue in Indonesia, characterized by high prevalence rates and increasing global antibiotic resistance This study aimed to evaluate the antibacterial activity of ethanol extract of Aloe vera against the growth of Propionibacterium acnes and Pseudomonas aeruginosa. An experimental laboratory design was employed for this research. The extract was obtained through maceration using 96% ethanol and tested using the disk diffusion method. The study compared three concentrations of the extract 20%, 40%, and 60% against ciprofloxacin as a positive control, and 1% carboxymethyl cellulose (CMC) as a negative control. The average inhibition zone diameters against Propionibacterium acnes at concentrations of 20%, 40%, and 60% were 10.55 mm, 11.66 mm, and 12.98 mm, respectively. For Pseudomonas aeruginosa, the inhibition zones measured 9.68 mm, 12.25 mm, and 13.43 mm at the same concentrations. In conclusion, antibacterial activity of Aloe vera extract against Propionibacterium acnes and Pseudomonas aeruginosa falls into the strong category, with the highest inhibition observed at a concentration of 60%. Keywords: Aloe vera; antibacterial activity; Propionibacterium acnes; Pseudomonas aeruginosa Abstrak: Lidah buaya (Aloe vera (L.) Burm. f.) dikenal memiliki potensi antibakteri, terutama terhadap bakteri penyebab infeksi kulit seperti Propionibacterium acnes dan Pseudomonas aeruginosa. Infeksi kulit menjadi masalah kesehatan penting di Indonesia, dengan prevalensi tinggi dan peningkatan resistensi antibiotik global. Penelitian ini bertujuan untuk mengetahui aktivitas antibakteri ekstrak etanol lidah buaya terhadap pertumbuhan Propionibacterium acnes dan Pseudomonas aeruginosa. Jenis penelitian yang digunakan ialah eksperimental laboratorium. Ekstrak diperoleh melalui maserasi menggunakan etanol 96% kemudian diuji menggunakan metode difusi cakram. Uji dilakukan dengan konsentasi ekstrak 20%, 40%, dan 60%, ciprofloxacin sebagai kontrol positif dan CMC 1% sebagai kontrol negatif. Hasil nilai rerata zona hambat terhadap Propionibacterium acnes pada konsentrasi 20%, 40%, dan 60% secara berurutan, yaitu 10,55 mm, 11,66 mm, dan 12,98 mm, sedangkan terhadap Pseudomonas aeruginosa, yaitu 9,68 mm, 12,25 mm, dan 13,43 mm. Simpulan penelitian ini ialah daya hambat ekstrak lidah buaya terhadap Propionibacterium acnes dan Pseudomonas aeruginosa termasuk kategori kuat dengan zona hambat tertinggi pada konsentrasi 60%. Kata kunci: lidah buaya; antibakteri; Propionibacterium acnes; Pseudomonas aeruginosa